2017
DOI: 10.1186/s12882-017-0565-y
|View full text |Cite
|
Sign up to set email alerts
|

Association between pulmonary function and renal function: findings from China and Australia

Abstract: BackgroundThe relationship between obstructive lung function and impaired renal function is unclear. This study investigated the dose-response relationship between obstructive lung function and impaired renal function.MethodsTwo independent cross-sectional studies with representative sampling were applied. 1454 adults from rural Victoria, Australia (1298 with normal renal function, 156 with impaired renal function) and 5824 adults from Nanjing, China (4313 with normal renal function, 1511 with impaired renal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Study participants' height was measured to the nearest 10th of a centimeter without wearing shoes. Both in Nanjing and Hefei surveys, above measurements were made by trained observers who were all asked to attend a training session to learn the standardized protocol of measurement techniques [8]. Study participants' body mass index was calculated by their body weight (unit: kg) divided by the square of their height (unit: meter).…”
Section: Clinical Measurementsmentioning
confidence: 99%
“…Study participants' height was measured to the nearest 10th of a centimeter without wearing shoes. Both in Nanjing and Hefei surveys, above measurements were made by trained observers who were all asked to attend a training session to learn the standardized protocol of measurement techniques [8]. Study participants' body mass index was calculated by their body weight (unit: kg) divided by the square of their height (unit: meter).…”
Section: Clinical Measurementsmentioning
confidence: 99%
“…In a study comprising 1246 men, Jung et al [ 14 ] revealed that male smokers had lower FEV1 and FVC in cases of albuminuria. Yu et al [ 16 ] found that in a cohort comprising 1454 Australian and 5824 Chinese individuals, an increased risk of reduced renal function was related to obstructive lung function, and that FEV1 and FVC < 3.05 L increased the risk of impaired renal function. A small Japanese study also reported that reduced GFR is associated with reduced pulmonary diffusing capacity [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…When we compared the functional trend in the CLAD and in the non-CLAD groups, the only statistically significant difference was found in the 12th month: %∆FVC; FEV 1 and FVC progressively increased in the non-CLAD group, probably due to ameliorative effects of everolimus on renal function; indeed it has been demonstrated that there is a non-linear dose-relationship between eGFR and FEV 1 and FVC. 20 In patients with chronic kidney disease, fluid overload together with increased pulmonary capillary permeability are closely associated with restrictive and obstructive respiratory abnormalities, as demonstrated in patients who underwent hemodialysis. 21 Even in the CLAD group, we observed a non-statistically significant and transient improvement of both FEV 1 and FVC after 1 month, but, subsequently, these parameters worsened.…”
Section: Discussionmentioning
confidence: 99%